Comparing Chinese and Indian Banks and their Socialist versus Capitalist Reforms - Liang, Priscilla (International Journal of Economics and Financial Issues, 2016)
Chinese and Indian banks have developed unique characteristics due to their distinctive reform paths and political regimes, yet they share attributes in common with banks of other emerging nations. After decades of reforms, banking systems in both countries remain relatively isolated and protected due to severe governmental interventions and strict policy directives. These limitations and drawbacks are in sharp contrast to China and India's present economic status, trade openness, and growth trajectories. This article describes the current status, strengths and weaknesses of Chinese and Indian banks; compares their commonalities and differences side-by-side; and traces banking developments and financial reforms to their particular socialist vs. capitalist political roots. Currently financial reforms are advancing in both countries with an aim to stimulate economic growth, yet their banks are burdened with rising bad debt and nonperforming loans. These article further addresses challenges of these banks and their policy implications. Keywords: Socialist Market Economy, Bank Reforms, Non-Performing Loans JEL Classifications: G21, P21